KAJIAN MACAM DOSIS PUPUK MAJEMUK NPK DAN PUPUK KANDANG TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT (Lycopersicum esculentum Mill.) - Ari Bahttiar Al Hafidh; Istiqomah Istiqomah; Ana Amiroh (AGRORADIX : Jurnal Ilmu Pertanian, 2021)
This research was conducted in Kadungrembug, Sukodadi District, Lamongan Regency. This study used a randomized block design (RAK) with a factorial pattern with 3 replications, consisting of 2 factors, namely the dose of npk fertilizer 100 kg/ha, 200 kg/ha, 300 kg/ha and The second factor is: without drum fertilizer, goat manure, chicken manure fertilizer. The purpose of this study was to determine the effect of giving a dose of NPK fertilizer to increase the growth and production of tomato. The application of goat manure and a dose of 100 kg/ha of NPK fertilizer was thought to have a better effect on the growth and production of tomato plants. So that the growth of tomato plants can grow optimally. The results of research that has been carried out on the treatment of doses of NPK fertilizer and manure on the growth and production of tomato plants treatment of doses of NPK fertilizer and manure on the growth and production of tomato plants can be concluded that there is an interaction with the combination manure and dose of NPK fertilizer parameters were plant height at 7, 14 and 21 days after planting, number of leaves at 7, 14 and 21 days after fruit number and fruit weight. The best treatment was obtained in the treatment of goat manure and NPK fertilizer dose of 100 kg/ha.